Indoor Air Pollution by PM2.5 and PM10 and their Potential Health Burden in Low, Middle and High-Income Residential Areas of Enugu Metropolis, Enugu State, Nigeria - Nebo, Antonia Nneka; Ugochukwu, Uzochukwu Cornelius; Ogbuene, Emeka Bright (Asian Journal of Chemistry, 2026)
Household sources of air pollution play a major role in determining the overall quality of life. Air pollution has been reported to greatly affect public health and contributes significantly to respiratory and cardiovascular disease prevalence. In this study, the concentration values of indoor PM2.5 and PM10 were measured in different residential areas (Independence layout, New Haven layout and Ogui New layout) of Enugu Metropolis covering dry and wet seasons using Bosean K-600M portable multi-gas detector. The health burden across the three residential areas was determined using AirQ+ modeling software. In comparison with the middle- and low-income areas, the higher-income residential area (Independence layout) did not have significantly lower levels of PM2.5 in the dry season but did in the wet season. About 10 people are likely to suffer chronic obstructive pulmonary disease (COPD) in Independence layout whereas for the middle- and low-income areas (New Haven and Ogui New layout) about 15 people will suffer COPD. Furthermore, 5 and 16 people are likely to suffer from ischemic heart disease (IHD) and acute lower respiratory infections (ALRI) respectively in Independence layout whereas for Ogui New layout and New Haven, 6 and 20 people will suffer IHD and ALRI, respectively. These numbers are worrisome and justify the urgent formulation and implementation of measures by the government to reduce airborne particulate matter in the study area.